Building Bridges of Understanding between Islam and Christianity in Nigeria - Opeloye, Muhib O. (2014)
Of the great monotheistic faiths having Abrahamic descent, Islam and Christianity enjoy the widest universal acceptance. Islam with about 1171 million adherents has 23.2% of the total world population which stands at about 5 billion, while Christianity with about 1424 million adherents attracts 29%. The adherents of the two religions therefore constitute more than half of the world population. Nigeria as a nation has a substantial percentage of the world population of Muslims and Christians. Archbishop John Onaiyekan makes a correct observation when he says: "Nigeria is one of the greatest Islamo-Christian nations in the world." What the archbishop means by this is that Nigeria is about the only country in the world where one finds a very large population of Muslims living side by side with a large population of Christians. There are nations with fairly large population of Muslims and Christians but more often than not we find one dominant over the other. Where Muslims and Christians are fairly balanced, the population would not be as large as Nigeria's. Though we cannot ascertain the actual population of the Muslims and Christians of this country because religious affiliation was not put into consideration during the 1991 controversial headcount, what is however certain is that the giant North remains the stronghold of Islam in spite of intensity of the Christian evangelism going on in the area, while the dominance of Christianity in the South East remains unchallenged. It is in the South-West that the two faiths attract a balanced population of adherents. The large population of Muslims and Christians in Nigeria gives the country an advantage of being a nation to be reckoned with in the global search for religious peace and harmony.